Yotsuba&!. 5 - Azuma, Kiyohiko (ADV Manga, 2007)
Yotsuba is a green-haired and wide-eyed girl who always has her befuddled neighbors' and friends' heads spinning with her energy. The comics series describes the hilarious exploits of the strange, out-of-this-world girl in her new town.